2013
DOI: 10.3917/mav.060.0102
|View full text |Cite
|
Sign up to set email alerts
|

Les effets de l'image du magasin sur le capital marque : une étude à travers les circuits de magasin

Abstract: Le but de cet article est d’examiner l’association l’image du magasin et le capital marque. Un échantillon des données de panel et d’enquête constitué de 1867 ménages, 11 magasins sur une période de 6 ans est étudié. Les résultats montrent que les dimensions de l’image du magasin sont associées au capital marque. Cependant, cette influence varie en fonction des circuits de magasin. Plus précisément, l’image accès est le plus important déterminant du capital marque dans les supermarchés et les hypermarchés bien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…Overall, consumers tend to base their format adjustment strategies on personal characteristics instead of marketing policy variables when crisis intensity is high. Therefore, this research completes previous studies on the relationship between store format and brand purchase behaviour (Zielke, 2010;Kaswengi, 2013;Kumar and Roy, 2013) and helps to better understand how specific retail formats are affected when crisis hits.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 57%
See 3 more Smart Citations
“…Overall, consumers tend to base their format adjustment strategies on personal characteristics instead of marketing policy variables when crisis intensity is high. Therefore, this research completes previous studies on the relationship between store format and brand purchase behaviour (Zielke, 2010;Kaswengi, 2013;Kumar and Roy, 2013) and helps to better understand how specific retail formats are affected when crisis hits.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 57%
“…For example, Kaswengi (2013) found that the impact of the store's marketing elements (e.g. access, price) on brand equity is different depending on store formats.…”
Section: Brand Choice In Different Store Formats In Crisis Periodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Kaswengi (2013) goes beyond the notion of consumers' attitudes and shows that the store image is a determinant of the brand equity of the SB. Ramaroson and Kaswengi (2013) add that this relationship between the store image, broken down into different dimensions, and the brand equity of the SB is moderated by the type of SB.…”
Section: Role Of the Retailer And Of The Storementioning
confidence: 99%